KONSENTRASI DAERAH PERHOTELAN DI KAWASAN DANAU TOBA - Syahrial Syahrial; Lincolin Arsyad (Convergence: The Journal of Economic Development, 2020)
In today's modern world, the number of hotels and other accommodations is increasing in Indonesia in general and in the province of North Sumatra in particular. The same situation also occurs in the Toba lake region which covers seven districts surrounding Toba lake with a number of hotels that vary in each district. This study aims to analyze the possibility of classification of the hospitality area concentration in the Toba lake region and analyze the shift in the classification of the hospitality area concentration in the Toba lake region. Panel data used will be analyzed using the method of classification analysis of the hospitality area concentration in the  Toba lake region. Then it will be assisted by geographic information system analysis as a visualization tool for maps of hospitality areas in the  Toba lake region. This research shows that the Toba lake region consists of two classifications, namely:  the classification of the main area of hospitality that cover three district  and tthe non-concentration classification of hospitality areas that includes four districts. During the study period, the shift in the classification of the hospitality area concentration were not found in the Toba lake region.   Keywords :  Geographic Information System 1, Hospitality Area Concentration 2